The Influence of Self-Efficacy and Peer Conformity on Academic Dishonesty in Purbalingga ‘X’ Vocational High School Students - Ghoni, Fathi Abdul; Noveni, Nia Anggri; Nur'aeni, Nur'aeni; Suwarti, Suwarti (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Vocational high school students need to have high integrity to be able to complement their skills, so that in the future, these students can meet the needs of the world labour market. Students who engage in academic dishonesty often have low self-efficacy and are affected by peer conformity. This study empirically examines the effect of self-efficacy on academic dishonesty, the effect of peer conformity on academic dishonesty, and the combined effect of self-efficacy and peer conformity on academic dishonesty among students at SMK